The Existence of Moncak Dance in South Tapanuli Community - Ina Refida Daulay (Universitas Negeri Medan, 2016)
This research is a study on the existence of Dance Moncak community South Tapanuli. The purpose of this study was to describe the existence of Dance Moncak community South Tapanuli.In the discussion of this study, used the theories related to the topic of writing, such as understanding Moncak Dance, Dance Moncak history and theoryof existence.The methods used to discuss the existence of Dance Moncak in South Tapanuli Society is a qualitative descriptive method.The population in this study as well as a sample, including traditional leaders, artists and dancers. Collection techniques include literature studies, interviews, observation and documentation. Based on the research which had held, it was known that Moncak Dance in South Tapanuli community was a chronology of an event of someone called Siraja Lottung who fight with tiger. Until now, it was not known the existence of Moncak dance in South Tapanuli start in what century. It is not found yet the scripture about the beginning of Moncak dance in South Tapanuli community. However theelders and Art Figure of South Tapanuli community said that Moncak was exist before the arrivalof Islam in South Tapanuli about 800 AD. In 1960 until 1980, Moncak was held as entertainmentand introduced to people of South Tapanuli. Nowaday the opponent of Moncak dancer was no tiger anymore, but human that is Moncak dancer. After the development of era, Moncak was held become a dancing that is Moncak dance that has plot and accompanied by music, where the community of South Tapanuli themselves didn’t know who made Moncak becomes a dance. Moncak dance event often took place in large field on Idul fitri as people entertainment. This eventdone in afternoon at first day of Idul fitri for a week. There are several young people called Pemoncak ( the one who expert in Moncak dance ).